Influencia del Proyecto Lean en el desempeño de los promotores de servicios de la sucursal trujillo del banco de credito del Perú. - Solórzano Polo, Soledad Katia (2011)
The research is applied according to the aim pursued and according to the research design is descriptive. This research was conducted in order to know how the Project Lean affects the performance in service promoters Trujillo Branch of Credit Bank of Peru. Participated 27 service promoters, as respondents, giving them a list of questions that included the two variables under study. The results are reported in statistics and graphs for further information. The results were: all service promoters know the main objectives of the Project Lean; they are very satisfied with the changes incurred. . Similarly, know their performance indicators and considered that the Project Lean positive influence (Excellent) in performance.